Serum immunoglobulin levels as a predictive factor for a better outcome of non-atopic childhood asthma - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (WILEY, 2011)
P>Childhood asthma is a heterogeneous condition with different phenotypes. Hereby, we aimed to study impact of serum immunoglobulin levels on clinical phenotypes and outcome of asthma. Seventy-eight children (M: 26, F: 52) aged less than 10 yrs (mean = 8.56 +/- 3.23 yrs) and diagnosed as mild-moderate persistent asthma, followed up for at least 1 yr were included into the study. Asthmatic children were divided into two groups based on serum immunoglobulin levels at admission and were evaluated with respect to demographic data, allergic sensitization, symptom scores, medication usage, pulmonary functions, and non-specific bronchial hyper-reactivity. The age at onset of symptoms (40.88 +/- 32.02 vs. 23.04 +/- 26.97 months) was significantly younger in children with hypogammaglobulinemia (n = 28) compared to normogammaglobulinemia group (n = 50) (p = 0.016). Mean follow-up duration was 3.8 +/- 2.1 yrs. Atopic sensitization rate was higher in those with normal immunoglobulin levels (81.2% vs. 17.9%), (p < 0.0001). Normal serum immunoglobulin levels were associated with atopic asthma (OR, 4.5; 95% confidence interval (CI): 2.0-10.1). For the prediction of atopic asthma, having normal immunoglobulin levels yielded predictive values of: sensitivity = 88.6%, specificity = 71.8%, positive predictive value = 81.1%, negative predictive value = 82.1%. Furthermore, percentages of atopic dermatitis and allergic conjunctivitis, elevated serum total IgE levels, eosinophilia, and bronchial hyper-reactivity were more common in normogammaglobulinemia with asthma group (p = 0.040, p = 0.003, p = 0.024, p = 0.030, p = 0.040, respectively). Although marked reductions in asthma scores and inhaled corticosteroid usage were observed in both groups over time, the rate of decline was significantly higher and earlier in hypogammaglobulinemia group (p = 0.0001, p = 0.004, respectively). In conclusion, asthmatic children with hypogammaglobulinemia presented at an earlier age, with lower rates of atopy, and earlier clinical improvement accompanied with earlier discontinuation of inhaled corticosteroids than children with normal immunoglobulin levels. Our data demonstrated that in children currently named as early-onset non-atopic asthma, hypogammaglobulinemia might be accompanying, providing evidence for a different phenotype of childhood asthma.
Keywords: atopy; childhood asthma; hypogammaglobulinemia; transforming growth factor-beta; TRANSIENT HYPOGAMMAGLOBULINEMIA; BRONCHIAL HYPERRESPONSIVENESS; T-CELLS; ATOPY; INFECTIONS; CHILDREN; ILLNESS; INFANCY